Good governance and contemporary Islamic political thought: towards an applied model - Salim, Toha; Akhmetova, Elmira (The London Central Mosque Trust Ltd., 2018)
This article discusses the topic of good governance in Islam as a part of the main objectives of the Sharī‛ah through studying the case of the Arab Spring in Egypt. It addresses the historical and ideological roots that led to the failure of Islamists in Egypt in establishing good governance. The article also addresses the crisis inherent in Islamist thought to overcome challenges faced in the realm of good governance. Islamic sources provide the principles that can serve as the foundations of good governance in the contemporary world. This article finds that good governance means a set of institutions and policies that can effectively and successfully address the social, economic and political issues for the betterment of humanity. By analysing the Traditionalists, the Salafists, and the Reformists - the three main trends in contemporary Islamic political thought - the paper suggests that the weaknesses of these trends in understanding good governance and Maqāṣid-based political thought of Islam were the main reasons which contributed to the failure of the Arab Spring in Egypt. The paper ends by suggesting that Islamic jurisprudence and ethics should play an effective role in directing the contemporary Islamic political thought towards a model of good governance, while Maqāṣid al-Sharī‛ah is a necessary tool to widen the scope of the application of Islamic ethos in the contemporary context.